Employee Daily Report Application Using Flutter Framework (Case Study: PT. Planet Selancar Mandiri) - Setiawan, Panji Rachmat; Fahturrahman, Rizki; Fadhilah, M Rizki (IT Journal Research and Development, 2023)
Planet Surf Retail company is a company that moves under PT. Planet Selancar Mandiri management has the first Planet Surf store located at Galleria Shopping Mall, Jogjakarta, since 1997 and still operates. Planet Surf has 54 stores spread across 31 cities throughout Indonesia and continues to grow to meet customer fashion needs. Each store has one leader and eight to ten employees. Nowadays, Planet Surf still uses third-party applications to help their jobs daily. The employees report their activity, employment, and progress using third-party applications, and the leader sees it. But the problem is third-party applications can not organize their report by name, date, and category. It makes there a condition that the leader misses seeing employees' reports, employees find it hard to report their activities, and misunderstandings between employees and the leader. In this research, the Author tries to develop an Android application to see if it can help employees and leaders finish their jobs. Features from the Application are daily reports, job reports, and progress reports, and the leader can create reports for all employees.